Bioprospecting of Microbes for Valuable Compounds to Mankind - Nurul-Syakima Ab Mutalib; Sunny Hei Wong; Hooi-Leng Ser; Acharaporn Duangjai; Jodi Woan-Fei Law; Shanti Ratnakomala; Loh Teng-Hern Tan; Vengadesh Letchumanan (Progress in Microbes and Molecular Biology)
The most biological multiplicity on this planet is almost certainly concealed in soils. Many valuable bacteria had been extensively dispersed in soils worldwide, with soils from terrestrial, desserts and Antarctic. Hence, soils become an intensively utilized ecological niche for the inhabitants to generate various useful biologically active natural products such as antibiotics, antifungal, antiviral, antioxidant, neuroprotection, anticancer and other important compounds. Bacteria including Actinobacteria have been exceptionally valuable for the pharmaceutical industry due to their limitless capability to generate secondary metabolites with various biological activities and chemical structure. Therefore, this article aims to provide critical insight of bioprospecting of microbes for valuable compounds to mankind.